1981
DOI: 10.1088/0022-3727/14/11/006
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of solid particle erosion mechanisms

Abstract: The erosion of a surface by a stream of solid particles is examined by considering the arrival times of the particles on the surface. The treatment first proposes a new concept, an 'impact zone', and then considers the arrival of the particles on one zone as a queuing process. The rate of erosion of ductile metals is predicted using simple arguments from probability theory. A comparison of the mechanisms of erosion has been made using this analysis as a basis for models. Results indicate that not all of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…4. The results are also in accordance with the common observation that the erosion rate (volume of material removed per mass of particle blasted) initially increases with increasing particle mass dose, before reaching a steady state [35], indicated by the linear portions of the curves in Fig. 4.…”
Section: Predicted Erosion At Various Angles Of Attacksupporting
confidence: 91%
See 1 more Smart Citation
“…4. The results are also in accordance with the common observation that the erosion rate (volume of material removed per mass of particle blasted) initially increases with increasing particle mass dose, before reaching a steady state [35], indicated by the linear portions of the curves in Fig. 4.…”
Section: Predicted Erosion At Various Angles Of Attacksupporting
confidence: 91%
“…The simulation can be used to explain the commonly observed phenomenon [35] that the erosion rate initially increases with particle dose, before reaching steady state. For example, Fig.…”
Section: Development Of Steady State Erosion Rate Due To Cooperative mentioning
confidence: 99%
“…Andrews performed some important analyses of (i) the effect of flux rate on the erosion of a surface by impacting particles [88] and (ii) the effect of particle collisions in the neighbourhood of an eroding surface [89]. Uuemois and Kleis [90] and Tilly and Sage [91] had noted that the mass loss per unit mass of erodent impacting declined for high flux rates.…”
Section: Multiparticle Studiesmentioning
confidence: 99%
“…This allowed the temperature rise per impact to be estimated. In turn, this allowed the minimum flux rate needed for thermal runaway to be estimated using Andrews' thermal flux analysis [88].…”
Section: Polymersmentioning
confidence: 99%
“…The authors suggested that the behaviour of the rubber was due to the increase in its temperature during erosion. This build up of heat in a target during erosion was also discussed by Andrews (1981) and Walley et al (1984). To quote directly from the latter paper, 'the eroding surface will rise in temperature if the rate of work done on it exceeds the rate at which heat can flow away through conduction, radiation or forced convection.…”
Section: Introductionmentioning
confidence: 95%